2015
DOI: 10.14214/df.207
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for renewable energy education (REE) in elevating youth energy and environmental awareness in Jordan

Abstract: Renewable Energy Education (REE) is an evolving public education approach that ultimately aims to elevate public awareness and cultivate their support toward renewable energy (RE) development. Young citizens are the pacesetters of RE development if equipped with the necessary knowledge and skills. There is, however, a lack of research studies aimed at exploring and understanding young citizens' perceptions and attitudes toward RE, particularly in developing countries. Jordan is an example of a fossil fuel-addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…They showed a limited degree of self-awareness and knowledge of young people on this subject (the results are different from those obtained by the study's authors). (Zyadin 2015) states a shortage of research conducted to examine and learn how young people percept and what attitudes they present about RES, especially in developing countries. His study also showed that mainly women preferred renewable energy sources.…”
Section: Resultsmentioning
confidence: 99%
“…They showed a limited degree of self-awareness and knowledge of young people on this subject (the results are different from those obtained by the study's authors). (Zyadin 2015) states a shortage of research conducted to examine and learn how young people percept and what attitudes they present about RES, especially in developing countries. His study also showed that mainly women preferred renewable energy sources.…”
Section: Resultsmentioning
confidence: 99%
“…Attitudes are essentially a construct of social psychology (Milfont and Duckitt 2010) and provide a potential advantage for the understanding and prediction of human behavior, and that attendance to attitude brings changes in behavior (Milfont and Duckitt 2010;Zyadin 2015). This latent construct cannot be measured directly but inferred from overt actions and can have immediate influence on closely related behavior (Zyadin 2015).…”
Section: Forest Certification In the Russian Federation: Challenges Amentioning
confidence: 99%
“…Attitudes are essentially a construct of social psychology (Milfont and Duckitt 2010) and provide a potential advantage for the understanding and prediction of human behavior, and that attendance to attitude brings changes in behavior (Milfont and Duckitt 2010;Zyadin 2015). This latent construct cannot be measured directly but inferred from overt actions and can have immediate influence on closely related behavior (Zyadin 2015). Attitudes consist of beliefs, feelings, and emotions about the object (FC in this case) and the behavioral elements of attitudes may surface as actions and responses within social and cultural boundaries and in contexts such as path-dependent or state dominant social phenomena (Milfont and Duckitt 2010;Zyadin 2015).…”
Section: Forest Certification In the Russian Federation: Challenges Amentioning
confidence: 99%
See 1 more Smart Citation
“…Although they completed the nature of renewable energy correctly, this situation varies according to the gender and school types of the students. In addition, according to Zyadin's (2015) study, two-thirds of the installation of solar energy and wind energy turbines in their regions is in relation to their knowledge of RES. Topçu and Atabey (2017) concluded in the study carried out with 31 seventh grade students in the city center of Muğla that the students developed their argumentation skills during the field trip they organized to thermal, wind, and hydroelectric power plants in their region.…”
Section: Introductionmentioning
confidence: 99%